IMPROVING JOB PERFORMANCE BY STRENGTHENING WORK MOTIVATION, ORGANIZATIONAL CLIMATE, TRANSFORMATIONAL LEADERSHIP, AND GROWTH MINDSET: Empirical Study on Regular Teachers of Private Junior High School Associations in Depok City - Arief Hidayat; Prof. Dr. Sri Setyaningsih; Dr. Dian Wulandari (JF Publisher, 2024)
Education will proceed well when it is supported by adequate teacher competence, able to improve their performance, have discipline and be able to provide exemplary for their students. If teachers do not provide a good performance, the implementation of education will not be as expected. The role of teachers is very important in achieving the success of the education and learning process. The function and role of teachers cannot be replaced by technological advances such as advanced media. The objectives of this research are to find out the strategies and methods in improving teachers’ performance through strengthening the organizational climate, transformational leadership, growth mindset, and work motivation. This research used quantitative research with survey method. While the data analysis techniques used in this research used path analysis techniques and SITOREM analysis. This research was conducted in private junior high schools in Depok, West Java. There are 109 private junior high schools in Depok City distributed in 11 sub-districts, which are Sukmajaya, Tapos, Pancoran Mas, Cimanggis, Sawangan, Cilodong, Bojong Sari, Cipayung, Beji, Limo, and Cinere. Based on the research results and discussion, the general conclusion of this research is that there are several strategies for improving teacher performance, which is strengthening the variables of organizational climate, transformational leadership, work motivation, and growth mindset, such as ongoing professional development; supportive feedback mechanisms; and integrating technology tools and resources into teaching practices.